New Explicit and Exact Solutions for the Klein-Gordon-Zakharov Equations (Communications in Mathematical Research, 2021)
In this paper, based on the generalized Jacobi elliptic function expansionmethod, we obtain abundant new explicit and exact solutions of the Klein-Gordon-Zakharov equations, which degenerate to solitary wave solutions and triangle functionsolutions in the limit cases, showing that this new method is more powerful to seekexact solutions of nonlinear partial differential equations in mathematical physics.